Insights and interventions : essays in honour of Uma Chakravarti - Chakravarti, Uma; Roy, Kumkum (New Delhi : Primus Books, 2011)
Contributed articles.
Includes bibliographical references and index.
Keywords: WOMEN -- INDIA -- SOCIAL CONDITIONS; CASTE -- INDIA; FEMINISM